Health of Parents, Their Children’s Labor Supply, and the Role of Migrant Care Workers - Frimmel, Wolfgang; Halla, Martin; Paetzold, Jörg; Schmieder, Julia (Journal of Labor Economics, 2025)
We estimate the impact of parental health on adult children’s labor market outcomes. We focus on health shocks that increase care dependency abruptly. Our estimation strategy exploits the variation in the timing of shocks across treated families. Empirical results based on administrative data show a significant negative impact on the labor market activities of children. This effect is more pronounced for daughters and for children who live close to their parents. Informal caregiving is the most likely mechanism. The effect is significantly muted after a liberalization of the formal care market, which sharply increased the supply of foreign care workers.